The Specialized Hsp70 (HscA) Interdomain Linker Binds to Its Nucleotide-Binding Domain and Stimulates ATP Hydrolysis in Both cis and trans Configurations - Alderson, T. Reid (Biochemistry, 2014)
[Image: see text] Proteins from the isc operon of Escherichia coli constitute the machinery used to synthesize iron–sulfur (Fe–S) clusters for delivery to recipient apoproteins. Efficient and rapid [2Fe-2S] cluster transfer from the holo-scaffold protein IscU depends on ATP hydrolysis in the nucleotide-binding domain (NBD) of HscA, a specialized Hsp70-type molecular chaperone with low intrinsic ATPase activity (0.02 min(−1) at 25 °C, henceforth reported in units of min(–1)). HscB, an Hsp40-type cochaperone, binds to HscA and stimulates ATP hydrolysis to promote cluster transfer, yet while the interactions between HscA and HscB have been investigated, the role of HscA’s interdomain linker in modulating ATPase activity has not been explored. To address this issue, we created three variants of the 40 kDa NBD of HscA: NBD alone (HscA(386)), NBD with a partial linker (HscA(389)), and NBD with the full linker (HscA(395)). We found that the rate of ATP hydrolysis of HscA(395) (0.45 min(–1)) is nearly 15-fold higher than that of HscA(386) (0.035 min(–1)), although their apparent affinities for ATP are equivalent. HscA(395), which contains the full covalently linked linker peptide, exhibited intrinsic tryptophan fluorescence emission and basal thermostability that were higher than those of HscA(386). Furthermore, HscA(395) displayed narrower (1)H(N) line widths in its two-dimensional (1)H–(15)N TROSY-HSQC spectrum in comparison to HscA(386), indicating that the peptide in the cis configuration binds to and stabilizes the structure of the NBD. The addition to HscA(386) of a synthetic peptide with a sequence identical to that of the interdomain linker (L(387)LLDVIPLS(395)) stimulated its ATPase activity and induced widespread NMR chemical shift perturbations indicative of a binding interaction in the trans configuration.